Ergonomics/human factors and the future of work: A global systems perspective - Thatcher A; Acquah AA; Aublet-Cuvelier A; Becker R; Bentley T; Boatca ME; Braatz D; Cheng H-I; Coutarel F; Gangopadhyay S; Green N; Heaton N; et al. (Elsevier Limited, 2026)
In a webinar series hosted by the International Ergonomics Association, the Future of Work Committee of the International Ergonomics Association gathered inputs about the future of work from ergonomics/human factors (E/HF) experts representing different regions around the world. Through these insights, four global megatrends relevant to E/HF driving the future of work were identified: labour-market supply; work informality; technology; and climate change. Next, we applied an E/HF systems approach, using causal loop diagrams, to explore the unfolding interrelationships between these megatrends at a global level and with a national level example to determine what novel insights can be uncovered using systems analysis. We demonstrate the power of E/HF systems thinking that can enable national E/HF societies and regional think-tanks to move beyond a siloed approach to megatrends. We conclude with some high-level suggestions for E/HF to consider in order to meet the future of work challenges.
Keywords: Informal work; Artificial Intelligence; Climate change